"No Other Choice": Reasons for Emergency Department Utilization Among Urban Adults With Acute Asthma. (January 2014) - Lawson, Charlotte C.; Carroll, Kate; Gonzalez, Rodalyn; Priolo, Chantel; Apter, Andrea J.; Rhodes, Karin V.; Bernstein, Steven
Abstract Objectives Asthma is considered "ambulatory care–sensitive, " yet emergency department (ED) visits remain common. Few studies have examined how ED asthma patients choose their sites of urgent care. The authors explored reasons for asthma‐related ED use among adults. Methods From May to September 2012, semistructured qualitative interviews were conducted with a convenience sample of patients visiting a high‐volume urban ED for asthma. A piloted interview guide was used; it had open‐ended questions derived from clinical experience and a focus group of asthmatic adults who frequently use the ED for care. Interviews were conducted until theme saturation was reached. Interview transcripts and field notes were entered into NVivo 10 and double‐coded, using an iterative process to identify patterns of responses, ensure reliability, examine discrepancies, and achieve consensus through content analysis. Results Patients view their asthma symptoms in two categories: those they can manage at home and those requiring a provider's attention. Preferred site of acute asthma care varied, but most patients felt that they had little choice for acute exacerbations. Specific reasons for ED visits included wait times, acuity, insurance status, ED resources/expertise, lack of symptom improvement, lack of asthma medication, inability to access outpatient provider, referral by outpatient provider, and referral by friend or family member. Conclusions Barriers to urgent outpatient care may contribute to ED use for asthma. Additionally, patients with asthma exacerbations may not recognize a need for provider attention until the need is urgent. Efforts to identify patients with acute asthma early and to increase access to urgent outpatient care may reduce asthma‐related ED visits.